THE INFLUENCE OF COMPENSATION, LEADERSHIP AND MOTIVATION ON EMPLOYEE PERFORMANCE AT CV. ARTHENIS TRAVEL - Ulumiyah, Khoiriyatul; Utomo, Priyo; Arifin, Syamsul; Adhitya Pratama, Devangga Putra; Waloyo, Waloyo (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: The purpose of the present research is to outline the impact of compensation, leadership and encouragement for staff efficiency at CV. Arthenis Travel. Design/Methodology/Approach: Descriptive quantitative methods is used in this study. The research instrument was a questionnaire distributed to participantss. The All of the participants in the current research were CV staff members. Arthenis Travel, with thirty-three individuals. The entire sample is the method used for sampling. A multiple linear regression technique was used for the data analysis, while SPSS software was used for the data processing. Findings: According to the study's t-test results, the compensation variable (X1) has a computed t value that is less than the t table, specifically -2.011 < 2.045. This indicates that, to some extent, the compensation variables has no discernible and favorable impact on the performance of employees (Y) at CV. Arthenis Travel. Performance of employees (Y) at CV. Arthenis Travel is positively and significantly impacted by the leadership variable (X2), in light of the determined t quantity of 20.445 > 2.045, which is higher than the t table. The calculated t value for the motivation variable (X3) is higher than the t table, specifically 4.943 > 2.045. This indicates that the motivational variable exerts a considerable and advantageous effect on the performance of workers (Y) at CV. Arthenis Travel. The computed F value was determined to be bigger than the F table, specifically 122.093 > 2.93, due to the F test findings. This demonstrates how, all at once, the variables of motivation (X3), leadership (X2), and compensation (X1) have a favorable and noteworthy impact on the performance of employees (Y) at CV. Arthenis Travel. Research limitations/implications: The findings of this study are expected to be used as a reference by subsequent researchers. Practical implications: With the findings of this study, it is expected that CV. Arthenis Travel can create a supportive work environment, improving optimal employee performance. Originality/value: The present research is the initial inquiry carried out by researchers. at CV. Arthenis Travel on employee performance. Paper type: Research paper